"We Learnt that Being Together Would Give us a Voice": Gender Perspectives on the East African Improved-Cookstove Value Chain. Issue 4 (2nd October 2019) - Sesan, Temilade; Clifford, Mike; Jewitt, Sarah; Ray, Charlotte
ABSTRACT: Improved cookstoves (ICS) have been promoted for several decades, with little success. Advocates looking to drive uptake encourage greater involvement of women in ICS enterprises, on the largely unproven premise that women's participation in the value chain will enhance their financial bottom line while giving a boost to ICS sales. This paper tests the validity of that premise, using qualitative evidence from East Africa. The analysis shows gender-differentiated outcomes for enterprises across the value chain. Women-led enterprises are significantly underrepresented at higher levels of the chain, where sales volumes are highest. Value-chain positioning also influences access to key inputs like finance, potentially reinforcing the gender divide in enterprise performance. The findings challenge the dominant narrative in the ICS field about the inevitability of the link between market participation and economic empowerment for women and indicate a need to look beyond conventional market models to enhance financial outcomes for women.